Validação de método espectrofotométrico de UV-Vis para análise de dióxido de cloro em água - Nogueira, Tiago Rocha (2023)
In water treatment plants, the disinfection stage is of fundamental importance to ensure the safe consumption of drinking water, employing oxidizing agents with biocidal properties. Various techniques have been utilized in the disinfection stage, including the use of ultraviolet radiation, ozone, ultrasound/cavitation, advanced oxidative processes, and chlorination. The use of chloramines and chlorine dioxide has been adopted due to the low formation of persistent by-products. Chlorine dioxide, a yellow-colored and water-soluble gas with high biocidal capacity, has been widely disseminated due to its simplified in-situ production process, allowing concurrent use with production. Several techniques have been presented for monitoring chlorine dioxide in water at trace levels to meet potability standards established by regulatory agencies. However, monitoring disinfectant production systems has posed a significant challenge, as high gas concentrations in solution imply an increase in steps during the analysis process, resulting in greater measurement uncertainties. This study delves into the main reaction pathways for chlorine dioxide production and the techniques used to determine its concentration. A direct determination method using UV-VIS spectrophotometry has been developed and validated, enabling measurement in a fixed-volume cell and flow injection. The method was developed through tests that assess the best cuvette model for reading, the interference of optically active products and by-products, the pH range of application, and the optimization of operational parameters (temperature and flow) for the flow system. Subsequently, the method was validated following guidelines established by the National Health Surveillance Agency (ANVISA), the National Institute of Metrology, Quality, and Technology (INMETRO), and the Ministry of Agronomy, Livestock, and Supply, meeting efficiency standards that facilitate the safe, reliable, and autonomous use of the method in chlorine dioxide production systems in pharmaceutical industries and water treatment plants. Finally, a comparative study among techniques presented in the literature is included to evaluate the performance of the methods.